HUBUNGAN KEBERADAAN BREEDING PLACES DAN PRAKTIK BUANG SAMPAH DENGAN KEJADIAN DEMAM BERDARAH DENGUE (DBD) DI KOTA SEMARANG - Kintan Arifa Shafirin; Nur Endah Wahyuningsih; Suhartono Suhartono (Jurnal Kesehatan Masyarakat (Undip), 2016)
Central Java Province is one of the provinces with endemic for Dengue Haemorrhagic Fever (DHF) category. In 2013, highest morbidity dengue in the city of Semarang in amount of 98,57/100.000 population.The existence of breeding places was very essential in the existence of dengue vector breeding places because the more it will be more solid dengue vector population. The purposed of this research was to analyzed the relationship between the presence of breeding places and the eliminating garbages practice on the incidence of dengue in the city of Semarang in January 2011- April 2016. This research is an analytic observational study with case control study design. Samples were residents of Semarang were 41 cases and 41 controls (case control) and all patients of Dengue Haemorrhagic Fever in 2011 – April 2016. Methods of data analysis using univariate, and bivariate with Chi Square. Results showed there is no relationship between the presence of the entire breeding place (p = 1.000; OR = 1.000), and the eliminating garbages practice (p = 0.276; OR = 2.139) by the incidence of DHF in the city of Semarang in 2011-2016. The conclusions from this research are there is no relationship between the existence of the entire breeding place and the eliminating garbage practices with incidence of dengue. The suggestions from this research should be DKK Semarang consider P2PM program in cooperation BMKG for anticipate the increasing of DHF and communities should participate in the prevention of dengue by conducting 3M.